Mechanism of MicroRNA-375 Promoter Methylation in Promoting Ovarian Cancer Cell Malignancy. (30th April 2021) - Shu, Junjun; Xiao, Ling; Yan, Sanhua; Fan, Boqun; Zou, Xia; Yang, Jun
Objective: Ovarian cancer (OC) ranks one of the most prevalent fatal tumors of female genital organs. Aberrant promoter methylation triggers changes of microRNA (miR)-375 in OC. Our study aimed to evaluate the mechanism of methylated miR-375 promoter region in OC cell malignancy and to seek the possible treatment for OC. Methods: miR-375 promoter methylation level in OC tissues and cells was detected. miR-375 expression in OC tissues and cell lines was compared with that in demethylated cells. Role of miR-375 in OC progression was measured. Dual-luciferase reporter gene assay was utilized to verify the targeting relationship between miR-375 and Yes-associated protein 1 (YAP1). Then, Wnt/β-catenin pathway-related protein expression was tested. Moreover, xenograft transplantation was applied to confirm the in vitro experiments. Results: Highly methylated miR-375 was seen in OC tissues and cell lines, while its expression was decreased as the promoter methylation increased. Demethylation in OC cells brought miR-375 back to normal level, with obviously declined cell invasion, migration and viability and improved apoptosis. Additionally, miR-375 targeted YAP1 to regulate the Wnt/β-catenin pathway protein expression. Overexpressed YAP1 reversed the protein expression, promoted cell invasion, migration and viability while reduced cell apoptosis. Overexpressed miR-375 in vivo inhibited OC progression. Conclusion: Our study demonstrated that demethylated miR-375 inhibited OC growth by targeting YAP1 and downregulating the Wnt/β-catenin pathway. This investigation may offer novel insight for OC treatment.